The role of fat grafting on contracted breast implant capsules: A retrospective comparative histological and immunohistochemical study. Issue 3 (March 2022) - Pagliara, Domenico; Vitagliano, Stefano; Mangialardi, Maria Lucia; Pino, Valentina; Santoro, Angela; Mulè, Antonino; Barone Adesi, Liliana; Salgarello, Marzia
Summary: Capsular contracture, a common complication of breast implant reconstruction following postmastectomy radiotherapy (PMRT), represents a challenge for plastic surgeons. Regenerative surgery with multiple autologous fat grafts (lipobed) before replacing the implant has been proven to be a satisfactory approach in the radio-damaged breast. Currently, in literature, there are no data available on the histological features of irradiated capsules after regenerative surgery. We enrolled 80 patients after immediate subpectoral alloplastic breast reconstruction, with indication for revision surgery due to grade IV capsular contracture developed after PMRT. Forty patients were undergoing multiple fat grafting (lipobed group, mean age 48) and 40 patients were not undergoing multiple fat grafting (non-regenerative surgery (NRS) group, mean age 49). The removed capsules were addressed to histological and immunohistochemical assessment. The capsules of the lipobed group patients compared with NRS group patients showed: a lower mean thickness (602.17 versus 670.43 µm; P  = 0.013), a lower collagen fiber alignment (median value of angle deviation: 30.34 versus 18.38; P  = 0.001), a lower immunohistochemical positivity for myofibroblasts (α-smooth muscle actin [α-SMA] expression: 12.5% versus 52.5%; P  = 0.00), a higher immunohistochemical positivity for estrogen receptor-β (ER-β; 80% versus 20%; P  = 0.00), and a lower immunohistochemical positivity for estrogen receptor-α (ER-α; 53.3% versus 16.7%; P  = 0.00). The histological and immunohistochemical differences found are possibly due to alterations in the extracellular microenvironment determined by grafted fat.